The Relationship between Inclusive Leadership of the Head of the Room and Job Satisfaction of Nurses in the Inpatient Room of RSI Assyifa Sukabumi - Selpi Windiastia; Arfatul Makiyah; Hendri Hadiyanto (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Inclusive leadership emphasizes openness, respect, and appreciation of diversity in the workplace. In healthcare settings, particularly in nursing, leadership style significantly influences job satisfaction and quality of service. However, variations in leadership practices may impact the work environment and staff performance differently. Objectives: This study aimed to analyze the relationship between the inclusive leadership of ward heads and the job satisfaction of nurses in the inpatient rooms of RSI Assyifa Sukabumi. Methods: A quantitative, correlational analytic design with a descriptive approach was used. The study involved 73 nurses selected through stratified random sampling from a total population of 90 nurses. Data were collected using a validated and reliable questionnaire. Univariate analysis was used to describe respondent characteristics, while bivariate analysis using the Chi-Square and Fisher’s Exact Test was conducted to examine the relationship between inclusive leadership and job satisfaction. The study was carried out between November and December 2024. Results: Most nurses rated inclusive leadership as good (54.8%) or very good (43.8%), and job satisfaction as good (61.6%) or very good (34.2%). Bivariate analysis showed a statistically significant relationship between inclusive leadership and nurses’ job satisfaction (p = 0.041), as determined by Fisher’s Exact Test. Conclusions: The findings indicate that inclusive leadership by ward heads is positively associated with nurse job satisfaction. Strengthening inclusive leadership practices can contribute to a more supportive work environment, improved motivation, and better nursing performance, ultimately enhancing patient care quality.